Perceptions of SONARA’S Corporate Reputation by the Host Community, Limbe II Council Area, Cameroon - Divine, Ebong-Pende Epie; Ngange, Kingsley Lyonga; Ndode, Stephen N. (Advances in Social Sciences Research Journal, 2024)
This study examines how the population of Limbe II council area perceives the Cameroon National Refining Company Ltd (SONARA) in terms of its business activities, its relationship with this major stakeholder group, its respect for environmental ethics, and the contribution of the company to the socio-economic development of the area. The population under study is the Limbe II council area, made up of 11 communities with 42300 inhabitants. Two methods of data collection are used: survey and qualitative content analysis of SONARA’s corporate policy documents. The questionnaire was administered to 330 respondents. Findings suggest that the Limbe Festival of Arts and Culture (FESTAC) is the most prominent social event sponsored by SONARA. FESTAC also projects SONARA’s image most, and best promotes inhabitants’ cultural values. Findings also indicate that for SONARA to gain improved reputation in Limbe II, the corporation should give priority to indigenes of Limbe II municipality in holiday jobs and recruitments. Respondents equally affirm that it is necessary for SONARA to sponsor cultural, educational, health and related activities in Limbe II municipality; pay royalties to the Limbe II Council; and sponsor political campaigns. Empirical evidence show a statistically significant linear relationship (p= 0.000) between SONARA’s satisfaction of Limbe II community needs and a positive reputation that the Limbe II community has about the company. This also implies that the company needs to carry out a re-appraisal of its community management plan for the host communities in order to ensure that only projects that are directly relevant to the needs of the host communities (as indicated by the inhabitants) are embarked upon.